Alkene isomerization-hydroarylation tandem catalysis : indole C2-alkylation with aryl-substituted alkenes leading to 1,1-diarylalkanes - Yoshikai, Naohiko (2014)
A cobalt-N-heterocyclic carbene catalyst generated from CoBr2, imidazolium salt, and cyclohexylmagnesium bromide was found to promote the imine-directed C2-alkylation of indoles with nonconjugated arylalkenes through a tandem alkene isomerization–hydroarylation process, affording 1,1-diarylalkanes with exclusive regioselectivity. The feasibility of the tandem catalysis was demonstrated for allyl-, homoallyl-, and bishomoallylbenzene derivatives. The catalytic system is also applicable to a variety of β-substituted styrene derivatives. Mechanistic experiments using deuterium-labeled indole substrate and Grignard reagent provided insight into the cobalt-mediated C[BOND]H activation step, which likely involves exchange of the C2-hydrogen atom of the former and the β-hydrogen atoms of the latter.